MADURA DAN KEARIFAN BUDAYA LOKALNYA - LAILATUL QADARIYAH; JAMILIYA SUSANTIN (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2020)
There are two local cultures in Madura, the first, Taneyan Lanjhang is a group of houses (traditional settlements) in which it is inhabited by one or one of the descendants and the arrangement of his house from the earliest to the youngest being sorted from West to east. Second, Kompolan (a compound of studies and a compound). These two cultures are a Madurese culture to date still preserved. And both have to walk balanced, do not drop each other and do not judge each other, both must Tawasuth, I'tidal, and Tawazun. This tradition is Al-Muhafazhah. While the move is "al-Akhdzu" if the old generation perpetuated tradition with al-Muhafazhah, then the generation of Mudanyamenjadi tradition with "Al-Akhdzu". They should not clash with each other.